Application of exercise therapy in patients with chronic kidney disease-induced muscle atrophy: a scoping review - Jiawei Yin; Xiaotu Zhang; Zilin Wang; Zihan Qu; Xuefeng Sun; Yuqing Song; Hongshi Zhang (BMC, 2024)
Abstract Background The prevalence of muscle atrophy in patients suffering from chronic kidney disease (CKD) presents a significant challenge to healthcare providers, necessitating innovative approaches to management and care. Against this backdrop, this study embarks on a comprehensive review of literature concerning the application of exercise interventions in the nursing care of these patients. Such interventions are critical in addressing the debilitating effects of the condition, which include progressive loss of muscle mass and strength, adversely affecting patient mobility, quality of life, and overall survival. This review aims to identify the specific exercise modalities, contents, outcome indicators, and application effects associated with this intervention, in the context of the complex interplay of metabolic, inflammatory, and hormonal factors contributing to muscle wasting in CKD patients. By examining the efficacy of various exercise interventions, this study seeks to elucidate optimal strategies for mitigating the impact of CKD-induced muscle atrophy, thereby informing clinical practices and improving patient outcomes. Methods According to the method of a scoping review, nine databases (Cochrane, PubMed, EMBASE, Web of Science, ProQuest, Ovid, CNKI, Wanfang Data, and VIP) were searched until September 28, 2023. The included literature was screened, summarized, and analyzed. Results A total of 20 pieces of literature were included. Some types include aerobic exercise, resistance exercise, and aerobic combined resistance exercise. The exercise intensity primarily falls within the mild to moderate range, with a recommended frequency of 2 − 3 times a week, lasting 30 − 60 min each time. The types of outcomes encompassed in this study include body composition, functional testing, strength measurements, laboratory examinations, cardiopulmonary function assessments, and patient-reported outcomes. To varying degrees, exercise intervention positively impacts the subjects' physical activity ability, body composition, and skeletal muscle status. Currently, resistance training is the primary type of intervention used for preventing and treating CKD patients induced by muscle atrophy. Conclusion Exercise intervention can improve muscle strength, physical function, and quality of life in patients with CKD muscle atrophy. Therefore, patients should be fully informed of the effect of exercise intervention in the treatment of chronic kidney disease-induced muscle atrophy in future, so as to promote the standardized implementation of exercise intervention.